2023
DOI: 10.1101/2023.02.12.528175
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protease-Activated Receptor 2 (PAR2) expressed in sensory neurons contributes to signs of pain and neuropathy in paclitaxel treated mice

Abstract: Background and Purpose: Chemotherapy-Induced Peripheral Neuropathy (CIPN) is a common, dose-limiting side effect of cancer therapy. Protease-activated receptor 2 (PAR2) is implicated in a variety of pathologies, including CIPN. In this study, we demonstrate the role of PAR2 expressed in sensory neurons in a paclitaxel (PTX)-induced model of CIPN in mice. Experimental Approach: CIPN was induced in both PAR2 knockout/WT mice and mice with PAR2 ablated in sensory neurons via the intraperitoneal injection of pacli… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 103 publications
0
1
0
Order By: Relevance
“…There is accumulating evidence for the intricate cross‐talk between macrophages, glial cells and nociceptors in the development and maintenance of chemotherapy‐induced neuropathic pain, within both the peripheral and central nervous systems (Chen et al, 2020; Gao et al, 2022; Kume et al, 2023; Liu et al, 2019; Mei et al, 2023; Warwick & Hanani, 2013; Yan et al, 2019; Yu et al, 2020; Zhang et al, 2013, 2016). Studies have revealed that paclitaxel treatment activates immune and glial cells, resulting in the release of various pro‐inflammatory mediators, including TNF‐α, IL‐1β, IL‐6, IL‐23, IL‐36, stromal‐derived cell factor 1, CCL2 and CXCL1.…”
Section: Discussionmentioning
confidence: 99%
“…There is accumulating evidence for the intricate cross‐talk between macrophages, glial cells and nociceptors in the development and maintenance of chemotherapy‐induced neuropathic pain, within both the peripheral and central nervous systems (Chen et al, 2020; Gao et al, 2022; Kume et al, 2023; Liu et al, 2019; Mei et al, 2023; Warwick & Hanani, 2013; Yan et al, 2019; Yu et al, 2020; Zhang et al, 2013, 2016). Studies have revealed that paclitaxel treatment activates immune and glial cells, resulting in the release of various pro‐inflammatory mediators, including TNF‐α, IL‐1β, IL‐6, IL‐23, IL‐36, stromal‐derived cell factor 1, CCL2 and CXCL1.…”
Section: Discussionmentioning
confidence: 99%